2015
DOI: 10.1093/icvts/ivv362
|View full text |Cite
|
Sign up to set email alerts
|

Is cardiac magnetic resonance imaging as accurate as echocardiography in the assessment of aortic valve stenosis?: Table 1:

Abstract: A best evidence topic was written according to a structured protocol. The question addressed was: is cardiac magnetic resonance (CMR) imaging as accurate as echocardiography in the assessment of aortic valve stenosis? Altogether 239 papers were found using the reported search. Only 12 demonstrated the best evidence to answer the clinical question. Nine of these 12 papers found CMR to correlate well with transthoracic echocardiography (TTE) or transoesophageal echocardiography (TOE) in the evaluation of aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Serial monitoring is typically performed with transthoracic echocardiography (TTE), although cardiac magnetic resonance (CMR) can be a useful adjunct to TTE [2,3]. CMR is established as the gold standard for quantification of left ventricular volumes and function and may provide more reproducible data for aortic regurgitation quantification [4][5][6][7][8]. Furthermore, CMR does not suffer from limited acoustic windows which may be compromised in patients with prior intervention or thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Serial monitoring is typically performed with transthoracic echocardiography (TTE), although cardiac magnetic resonance (CMR) can be a useful adjunct to TTE [2,3]. CMR is established as the gold standard for quantification of left ventricular volumes and function and may provide more reproducible data for aortic regurgitation quantification [4][5][6][7][8]. Furthermore, CMR does not suffer from limited acoustic windows which may be compromised in patients with prior intervention or thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between CT and TTE AVA measurements was strong (r = 0.89) and the mean difference was 0.03 ± 0.05 cm2 . Because of the elliptical anatomy of LVOT, 2D TTE may underestimate the LVOT area.…”
mentioning
confidence: 86%
“…According to a systemic review, eight of 12 papers found CMR for the diagnosis of AS to have excellent reliability and reproducibility (low inter-and intraobserver variability) [2]. One study noted a sensitivity and specificity of 96% and 100%, respectively, when using CMR to detect AS diagnosed by cardiac catheterization (CC).…”
Section: Cmr Assessment Of As Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Diese ist sehr gut reproduzierbar und korreliert gut mit der in der transthorakalen und transösophagealen Echokardiografie bzw. der katheterbasiert gemessenen KÖF [5]. Die direkte Planimetrie ist daher in der CMR die bevorzugte Methode zur Bestimmung der KÖF.…”
Section: Cine-aufnahmenunclassified